Parallel independent voltage computing along dendrites of CA3 pyramidal neurons - Asako Noguchi; Satoshi Terada; George N. Zakka; Cliodhna O’Toole; Luke Reynolds; Michelle Ann Land; Balázs J. Rózsa; François St-Pierre; Attila Losonczy (Science, 2026)
Dendritic computation contributes to information processing in cortical circuits. Hippocampal CA3 plays a central role in navigation, but how the dendrites of CA3 pyramidal neurons process information in vivo remains largely unknown. Using voltage imaging across dendrites and somata of CA3 pyramidal neurons during virtual reality–guided navigation in mice, we found that the dendritic arbor comprises multiple independent computational units that can dynamically couple to or dissociate from somatic activity, depending on behavioral conditions. Dendritic activity shapes subcellular representations of space, reward, and context through conditional coupling to the somatic output. Furthermore, spatially cotuned dendrites retain their coordination during sharp-wave ripples. These findings demonstrate that past, present, and future representations coexist within the dendritic arbor of CA3 pyramidal neurons, collectively shaping behaviorally relevant neuronal coding.